CO2 exchange and evapotranspiration across dryland ecosystems of southwestern North America. (19th April 2017) - Biederman, Joel A.; Scott, Russell L.; Bell, Tom W.; Bowling, David R.; Dore, Sabina; Garatuza‐Payan, Jaime; Kolb, Thomas E.; Krishnan, Praveena; Krofcheck, Dan J.; Litvak, Marcy E.; Maurer, Gregory E.; Meyers, Tilden P.; et al.
Abstract: Global‐scale studies suggest that dryland ecosystems dominate an increasing trend in the magnitude and interannual variability of the land CO2 sink. However, such analyses are poorly constrained by measured CO2 exchange in drylands. Here we address this observation gap with eddy covariance data from 25 sites in the water‐limited Southwest region of North America with observed ranges in annual precipitation of 100–1000 mm, annual temperatures of 2–25°C, and records of 3–10 years (150 site‐years in total). Annual fluxes were integrated using site‐specific ecohydrologic years to group precipitation with resulting ecosystem exchanges. We found a wide range of carbon sink/source function, with mean annual net ecosystem production (NEP) varying from ‐350 to +330 gCm −2 across sites with diverse vegetation types, contrasting with the more constant sink typically measured in mesic ecosystems. In this region, only forest‐dominated sites were consistent carbon sinks. Interannual variability of NEP, gross ecosystem production (GEP), and ecosystem respiration (Reco ) was larger than for mesic regions, and half the sites switched between functioning as C sinks/C sources in wet/dry years. The sites demonstrated coherent responses of GEP and NEP to anomalies in annual evapotranspiration (ET), used here as a proxy for annually available water after hydrologic losses. Notably, GEP and Reco were negatively related to temperature, both interannually within site and spatially across sites, in contrast to positive temperature effects commonly reported for mesic ecosystems. Models based on MODIS satellite observations matched the cross‐site spatial pattern in mean annual GEP but consistently underestimated mean annual ET by ~50%. Importantly, the MODIS‐based models captured only 20–30% of interannual variation magnitude. These results suggest the contribution of this dryland region to variability of regional to global CO2 exchange may be up to 3–5 times larger than current estimates. Abstract : Global‐scale studies suggest that drylands dominate an increasing trend in the magnitude and interannual variability of the land CO2 sink, but direct measurements are lacking; 25 eddy covariance sites in the water‐limited southwest of North America showed wide‐ranging carbon sink/source function, contrasting with the persistent sink typically measured in mesic ecosystems. Interannual variability of CO2 exchange was larger than for mesic regions, and half the sites switched between functioning as C sinks/sources in wet/dry years. CO2 exchanges were negatively related to temperature, in contrast to positive effects commonly reported for mesic ecosystems. MODIS‐based models captured only 20–30% of interannual variation, suggesting this dryland region may contribute 3–5 times more variability to global carbon and water cycles than current estimates.